2014
DOI: 10.1007/s12663-014-0624-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Lidocaine in Permanent Maxillary Teeth Removal Performed with Single Buccal Infiltration Versus Routine Buccal and Palatal Injection

Abstract: Purpose For many dental patients, palatal injection proves to be a very traumatic experience. Diverse methods have been suggested to reduce the discomfort of palatal injection. Nevertheless, the reliability of these methods is not obviously evident and they are not found to be universally effective. The desirable method to evade pain during palatal injection is just not to have one. Hence, the present study aims at investigating if lidocaine hydrochloride could provide palatal anesthesia in maxilla when only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Fan et al [17] and Kumaresan et al [18] indicated that routine palatal injection yielded significantly more discomfort than BI. The mean injection pain of BI alone was 0.91 (NRS), which falls in the mild pain category [18]. This was consistent with the values found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al [17] and Kumaresan et al [18] indicated that routine palatal injection yielded significantly more discomfort than BI. The mean injection pain of BI alone was 0.91 (NRS), which falls in the mild pain category [18]. This was consistent with the values found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The property of diffusion makes it suitable for a single buccal injection in avoiding a painful palatal injection [ 5 6 8 ]. However, there is insufficient literature regarding the diffusion of lidocaine, which is a commonly used drug and considered as the gold standard [ 4 9 ]. Therefore the present study was conducted to compare the efficacy and safety of 2% lidocaine HCl with 1:100,000 adrenaline and 4% articaine HCl with 1:100,000 adrenaline using single buccal infiltration for the extraction of bilateral maxillary premolars, with the hypothesis that there would be no significant difference amongst the two local anesthetic agents used as a single buccal infiltration technique in all outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The washout period between the interventions on both sides was 14 days. Other studies have reported a success rate of 92% in buccal infiltration with lidocaine for orthodontic extractions in the premolar region without a palatal injection [ 4 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations